Inflammation and Immunity Pathways Regulate Genetic Susceptibility to Diabetic Nephropathy - Gurley, Susan B. (Diabetes, 2018)
Diabetic nephropathy (DN) is a leading cause of end-stage renal disease worldwide, but its molecular pathogenesis is not well defined, and there are no specific treatments. In humans, there is a strong genetic component determining susceptibility to DN. However, specific genes controlling DN susceptibility in humans have not been identified. In this study, we describe a mouse model combining type 1 diabetes with activation of the renin-angiotensin system (RAS), which develops robust kidney disease with features resembling human DN: heavy albuminuria, hypertension, and glomerulosclerosis. Additionally, there is a powerful effect of genetic background regulating susceptibility to nephropathy; the 129 strain is susceptible to kidney disease, whereas the C57BL/6 strain is resistant. To examine the molecular basis of this differential susceptibility, we analyzed the glomerular transcriptome of young mice early in the course of their disease. We find dramatic differences in regulation of immune and inflammatory pathways, with upregulation of proinflammatory pathways in the susceptible (129) strain and coordinate downregulation in the resistant (C57BL/6) strain. Many of these pathways are also upregulated in rat models and in humans with DN. Our studies suggest that genes controlling inflammatory responses, triggered by hyperglycemia and RAS activation, may be critical early determinants of susceptibility to DN.